2015
DOI: 10.1186/s12913-015-1168-6
|View full text |Cite
|
Sign up to set email alerts
|

Errors in cause-of-death statement on death certificates in intensive care unit of Kathmandu, Nepal

Abstract: BackgroundDeath certificates (DC) are one of the most important medico-legal documents that physicians work through. DCs are extensively used in health statistics for epidemiological studies, and in health policy planning as a public health resource tool. Cause-of-death (COD) statement, which is vulnerable to various errors, is the vital part of a DC that has the potential to mislead the policy makers and statisticians. Hence, we evaluated and analyzed the errors prevalent in COD statement of DC.MethodsA retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 18 publications
0
50
0
2
Order By: Relevance
“…[13][14][15][16] Autopsy remains the standard against which clinician death certification accuracy is assessed. 3,[1][2][3][4][5][6][7][8][9][10][11][12][17][18] Despite many diagnostic medical advances, recent studies still report autopsy to reveal major missed diagnoses in roughly 17.7%-29% of cases. 3,[17][18][19] Even in cases in which autopsy was not performed, review of death certificates and corresponding medical records by autopsy pathologists reportedly reveals certification errors in up to 48%¬96% of cases, of which 34%-51% are major errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13][14][15][16] Autopsy remains the standard against which clinician death certification accuracy is assessed. 3,[1][2][3][4][5][6][7][8][9][10][11][12][17][18] Despite many diagnostic medical advances, recent studies still report autopsy to reveal major missed diagnoses in roughly 17.7%-29% of cases. 3,[17][18][19] Even in cases in which autopsy was not performed, review of death certificates and corresponding medical records by autopsy pathologists reportedly reveals certification errors in up to 48%¬96% of cases, of which 34%-51% are major errors.…”
Section: Discussionmentioning
confidence: 99%
“…Both nationally and internationally, it has been reported that medical students and non-pathology residents are poorly trained in death certification. 1,4,[21][22][23] In one survey of 590 residents from various US institutions, 76% reported having received no formal training in death certification principals, and when asked to complete a cause of death statement based on a sample scenario of a hospital urosepsis death, 77% performed suboptimally, with 45% incorrectly attributing the death to a cardiovascular event. 21 At our institution, death certification inaccuracies cannot be attributed to resident inexperience per se, as only fellows and attending faculty are tasked with certification; however, the death certification training provided to trainees who ultimately become fellows and attending faculty is admittedly limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some studies have questioned the eligibility of house officers, residents, physician assistants and other trainees in death certification. These interns are temporal workers at health facilities and are likely to spend less time with patients in most cases (Maharjan et al, 2015). Studies conducted in Greece recorded more specialist and consultants than interns (Filippatos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%